ملامح تربية إسلامية في المنظور القرآني (دراسة في سورة الفاتحة) - Syaifudin, Muh.; Ma'ruf, M.A.; Murtadho, Ahmad Ali (TAWASUT, 2021)
abstract This article attempts to describe the content of Surah Al-Fatihah from an educational aspect.By using the method of analysis of the Qur'anic interpretation (tahlili), the author traces the interpretations of Al-Qur’a both classical and contemporary. It is not an exaggeration to say that Allah is the educator of the universe with humans as the foremost beings who are affected by this project. In carrying out this mission, the Al-Qur'an is used as a medium as well as a means to take people step by step towards perfection. Al-Fatihah as the first chapter in the Al-Qur'an, also referred to as its mother, certainly cannot be separated from this great mission. Starting from basmalah, the affirmation of the name Allah Ar-Rahman Ar-Rahim seems to be a guide that every educator must base all his actions in the name of compassion, as Allah SWT. However, compassion here must be balanced with reward and punishment (verse: 4). The second stage to achieve success in education is high trust in educators. This is because the student will not be able to get the maximum result of knowledge if he has doubts about the teacher. Third, as the meaning of education is to walk the path to the goal, not to arrive at the destination instantaneously or to arrive at the destination in any way, then in verse 6, students are directed to walk the shirotol mustaqim, the straight path to the peak of happiness in the world and the hereafter. Finally, Surah Al-Fatihah is closed with a gesture to imitate the previous people. Successful people to imitate, perverted people to shun.